Cu(iii)triarylcorroles with asymmetric push–pull meso-substitutions: tunable molecular electrochemically catalyzed hydrogen evolution. Issue 21 (15th May 2017) - Liang, Xu; Niu, Yingjie; Zhang, Qianchong; Mack, John; Yi, Xiaoyi; Hlatshwayo, Zweli; Nyokong, Tebello; Li, Minzhi; Zhu, Weihua
Abstract : The A2 B type Cu(iii )triarylcorroles with meso -aryl push–pull substituents demonstrate that these compounds are highly efficient catalysts for modulating electrocatalyzed hydrogen evolution reactions (HERs). Abstract : The synthesis of four low symmetry A2 B type Cu(iii )triarylcorroles with meso -aryl substituents that provide electron donating (push) and withdrawing (pull) properties is reported, along with their structural characterization by NMR spectroscopy and X-ray crystallography. An analysis of the structure–property relationships in the optical and redox properties has been carried out by comparing their optical spectroscopy, electrochemistry, and spectroelectrochemistry to trends predicted in DFT and TD-DFT calculations. The results demonstrate that A2 B type Cu(iii )triarylcorroles are highly efficient catalysts for electrocatalyzed hydrogen evolution reactions (HERs) and that their reactivity can be modulated by changing the nature of the B-position meso -substituent.